Long term wear of complete contacts subject to fretting - Cartwright, R; Paynter, R; Hills, D; Nowell, D (2011)
The fully worn configuration of complete, square-edged contacts subject to fretting fatigue is found using a local asymptote, and this is applied to a specific example problem. There are three possible forms of solutions: (a) all wear is averted, (b) there is a finite amount of wear to a stable, fully adhered contact and (c) progressive wear gradually eroding the whole contact. The conditions under which each of these is the anticipated response are revealed. © 2011 Elsevier B.V.